Direct and indirect effects of work-family conflict on job performance - Ahmad, Aminah (Journal of International Management Studie, 2008)
A model is developed on the effects of work-family conflict on employees’ emotional exhaustion, job satisfaction and job performance based on the role theory and the conservation of resources theory as well as related studies. The model proposes that the consequences of work-family conflict can be traced through four different paths and the relationships between work-family conflict and the outcome variables are: 1) work-family conflict has a direct negative effect on the level of employees’ job performance; 2) work-family conflict tends to increase employees’ emotional exhaustion which will in turn lower the job performance level; 3) work-family conflict reduces employees’ job satisfaction which will in turn decrease the level of job performance; 4) work-family conflict leads to emotional exhaustion experienced by employees which will reduce the job satisfaction level and consequently lower the job performance level.